Gold‐Catalyzed 1, 2‐Diarylation of Alkenes. (11th May 2020) - Chintawar, Chetan C.; Yadav, Amit K.; Patil, Nitin T.
Abstract: Herein, we disclose the gold‐catalyzed 1, 2‐diarylation of alkenes through the interplay of ligand‐enabled Au I /Au III catalysis with the idiosyncratic π‐activation mode of gold complexes. Unlike the classical migratory‐insertion‐based approach to 1, 2‐diarylation, the present approach not only circumvents the formation of direct Ar−Ar′ coupling and Heck‐type side products but more intriguingly demonstrates reactivity and selectivity complementary to those of previously known metal catalysis (Pd, Ni, or Cu). Detailed investigations to underpin the mechanistic scenario revealed oxidative addition of aryl iodides to an Au I complex to be the rate‐limiting step owing to the non‐innocent nature of the aryl alkene. Abstract : Taking the path less chosen : By integrating ligand‐enabled Au I /Au III catalysis with the intrinsic π‐activation ability of gold complexes, an efficient 1, 2‐diarylation reaction of alkenes was developed (see scheme). The 1, 2‐diarylation reaction showed complementary reactivity and selectivity to established processes with palladium, nickel, and copper catalysts.